Reform of Building Permit Policy in Indonesia: Analyzing the Challenges and Problem-Solving - Indah, Anggun Rosa; Nurasa, Heru; Ningrum, Sinta (Universitas Teuku Umar, 2025)
The Indonesian government implemented a substantial change in building permit regulation through the transformation of the IMB (building permit) to PBG (building approval) as a result of the Omnibus Law on Job Creation Act. The policy reforms intend to increase investment and optimize the arrangement of buildings and environments to enhance disaster resilience and encourage sustainable development. During the implementation stage has resulted in several challenges such as lack of regulation and implementation guideline for district or city administrator, complexity of technical standard requirement for PBG, unclear technical recommendation letter from regional technical services, and insufficient PBG services related to human resources issues. This study aims to analyses the PBG implementation challenges experienced by the local government as well as the Indonesian community, to figure out the government's steps for tackling these public issues. Using multiple research methods including a literature review, a fishbone diagram, systems thinking, and SWOT analysis, this research finds the form of policy recommendation for effectively addressing the problems. This strategy includes intensive coordination with central government, in this case Kementerian PUPR, collaboration with licensing regional agencies, improvement support facilities to meet building standards, expanding monitoring of construction by enforcing penalties and strict sanctions, and setting up task force team to expedite the building permit approval, which could help boosting up local government income.